Posttraumatic Growth in Postlingually Deaf Patients With Cochlear Implants: The Effect of Stress-Coping Strategies, Sociodemographics, and Deafness-Related Factors - Kobosko, Joanna; Jedrzejczak, W. Wiktor; Porembska, D. Beata; Geremek-Samsonowicz, Anna; Skarzynski, Henryk (Frontiers in Psychology, 2021)
The aim of this study was to assess whether cochlear implant (CI) users who had been postlingually deaf developed a more positive outlook on life – so-called posttraumatic growth (PTG) – as a result of their disability and to examine how PTG related to their stress-coping strategies and personal circumstances. The study group consisted of 119 postlingually deaf CI users. The participants were asked to anonymously fill in several questionnaires: the Post-Traumatic Growth Inventory (PTGI), Coping Orientations to Problems Experienced (Brief COPE), and a form asking for personal details and factors related to their deafness and CI use. The PTG of postlingually deaf CI users was similar to that found with other severe health problems. Time since loss of hearing, and especially from receiving a CI, was positively correlated with PTG. The level of PTG was correlated with the particular coping strategies used, and differed between men and women. We found that development of PTG could emerge from both approach-oriented coping strategies (such as active coping and planning) and avoidance-oriented coping strategies (denial, self-distraction, and self-blame). Paradoxically, avoidance strategies could play a positive role in the development of PTG. This reinforces the idea, previously raised in the PTG literature, that such strategies exert a defensive and protective function – an "illusory" side of PTG that operates together with a positive constructive side, both of which help develop a sense of well-being.